2023
DOI: 10.31234/osf.io/axseu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Driver-pedestrian interactions at unsignalised crossings are not in line with the Nash equilibrium

Abstract: Modelling human-robot interaction in the road traffic context is an evolving yet understudied area. Recent developments in vehicle automation require simulations of such interactions, which can be achieved by computational models of human behaviour such as game theory. Game theory is a modelling paradigm that provides a good insight into road user behaviour by considering agents’ interdependencies. However, it is still unclear whether conventional game theory is suitable for modelling vehicle-pedestrian intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…First, there is the assumption that all players rationally maximize some utility function. Empirical evidence has shown that even in simple economic games [ 18 ], but also in driving behaviour [ 19 ] and traffic interactions [ 20 ], this assumption does not hold for human players. Second, game theory does not allow communication between the players—an aspect known to be important in interactive driving scenarios [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, there is the assumption that all players rationally maximize some utility function. Empirical evidence has shown that even in simple economic games [ 18 ], but also in driving behaviour [ 19 ] and traffic interactions [ 20 ], this assumption does not hold for human players. Second, game theory does not allow communication between the players—an aspect known to be important in interactive driving scenarios [ 3 ].…”
Section: Introductionmentioning
confidence: 99%